Hydrogel microsphere with high elasticity and super-lubricating property as well as preparation method and application of hydrogel microsphere
By introducing hectorite nanosheets and PMPC molecules into hydrogel microspheres, combined with microfluidics and surface grafting technology, the problem of hydrogel microspheres being difficult to combine high elasticity and super lubrication properties was solved, and the bone implant was achieved. Better application results in the field of repair.
Patent Information
- Application Number
- CN202411379180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing hydrogel microspheres are difficult to take into account high elasticity and superlubrication properties, resulting in limited application effects in the field of bone repair.
By synthesizing a photo-crosslinked GelMA monomer solution and mixing it with hectorite nanosheets, cross-linked hybrid hydrogel microspheres were prepared using microfluidic technology, and then PMPC molecules were introduced through surface grafting methods to achieve high elasticity and Combined with super lubrication performance.
The elastic modulus of hydrogel microfinance is controlled between 14Pa and 4000Pa, and the friction coefficient can be adjusted between 0.12 and 0.04, significantly improved its effect in bone injury repair.
Smart Images

Figure CN119331273A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a hydrogel microsphere with high elasticity and super lubricity, and a preparation method and application thereof. Background Art
[0002] Traditional hydrogel materials have inherent mechanical limitations, such as easy deformation due to low strength and brittleness despite poor elasticity, which poses a major obstacle to their widespread application. In the process of modifying hydrogels, researchers face a common dilemma, that is, how to strike a balance between "rigidity" and "toughness", "elasticity" and "lubricity".
[0003] Previous studies have shown that balancing the "toughness" and "stiffness" of hydrogels can be achieved through a variety of methods, such as constructing multi-network hydrogel systems, domain crosslinking, high-density dynamic bonding systems, or host-guest interactions. However, the integration of "elasticity" and "lubricity" properties in hydrogel structures has rarely been addressed. This gap mainly stems from the fact that enhancing "elasticity" relies heavily on enhancing the entanglement of polymer chains and the intermolecular forces between chain segments, thereby reducing the possibility of gel rupture during deformation through energy dissipation, resulting in high interchain friction and low water content. On the contrary, the "lubricity" property depends on the polymer molecular chains adsorbing a large number of water molecules to promote hydration lubrication. The strong binding with water molecules inevitably weakens the intermolecular forces between polymer chains, resulting in chain swelling, softening, increased deformation, and structural fragility. Therefore, both from a structural and theoretical perspective, the "dehydration" enhanced elasticity and "hydration" lubrication of hydrogels are essentially a contradictory relationship between "elasticity" and "lubricity".
[0004] The construction of elastic hydrogels mainly relies on methods such as increasing chain entanglement, inducing crystallization, and enhancing intermolecular forces. For example, Suo's team increased the entanglement density of long-chain polymers under low water content conditions. This dense entanglement network promotes tension transmission within the polymer chain, thereby preventing chain breakage caused by stress concentration and obtaining remarkable gel elasticity. Qiu's team designed polyvinyl alcohol hydrogels to achieve high-density crosslinking within the crystalline domains by reducing hydration and enhancing the salting-out effect. The dissipation of non-covalent energy in these regions contributes significantly to the observed elastic enhancement. Meanwhile, Yu's team created layered hydrogels through the careful assembly of nanostructured building blocks and a two-stage in situ polymerization process. This unique structure, characterized by highly curled interconnected and in situ cross-linked polymer networks between layers, endows the hydrogel with remarkable elastic strain capacity. Therefore, the main strategies for enhancing elasticity usually include increasing interchain density and friction, enhancing hydrophobic elasticity, and reducing water layer thickness and total water content, usually at the expense of lubricity.
[0005] Among the existing methods, although attempts have been made to improve the mechanical strength of hydrogel microspheres and maintain a low friction coefficient, the results obtained in current research are relatively limited, and it is impossible to achieve a good balance between high elasticity and low friction for hydrogel microspheres, thus affecting their effect on bone repair.
[0006] For example, it has been reported that the use of nano-lithium laponite can enhance the mechanical properties of hydrogels. However, the extent of the improvement is very limited, and it is difficult to significantly increase the elastic modulus of the composite hydrogel. At the same time, due to the trade-off of elasticity, the lubrication properties of the hydrogel cannot achieve ultra-low friction.
[0007] Therefore, how to provide a method for hydrogel microspheres with high elastic modulus and low friction coefficient, which can take into account both high elasticity and super lubricity, solve the contradiction between "elasticity" and "lubrication" of hydrogel microspheres, and better use them in the field of bone repair, has become a technical problem that needs to be solved urgently at this stage. Summary of the invention
[0008] The present invention is to solve the above technical problems, thereby providing a hydrogel microsphere with both high elasticity and super lubricity and its preparation method and application. The technical purpose of the present invention is to provide a hydrogel microsphere with high elastic modulus and low friction coefficient, which can well integrate the contradiction between "elasticity" and "lubricity", so that it has both high elasticity and super lubricity, so as to be better used for the repair of bone damage.
[0009] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0010] The present invention first provides a method for preparing hydrogel microspheres with both high elasticity and super lubricity, comprising the following steps:
[0011] (1) Synthesizing photo-crosslinked GelMA monomer solution;
[0012] (2) mixing the laponite nanosheets with the GelMA monomer solution obtained in step (1), and preparing laponite cross-linked hybrid hydrogel microspheres by microfluidic technology;
[0013] (3) The hydrogel microspheres obtained in step (2) are modified by a surface grafting method using 2-methacryloyloxyethyl phosphorylcholine and acrylamide to obtain hydrogel microspheres having both high elasticity and super lubricity.
[0014] The simultaneous existence of "high elasticity" and "high lubricity" is a unique feature of living organisms because of their tunable biological activity. However, in inanimate hydrogels, the enhanced elasticity of "dehydration" and the lubricating properties of "hydration" essentially create a contradictory relationship between "elasticity" and "lubrication". The present invention successfully developed a "living" biodegradable hydrogel microsphere through the above method to address this challenge. The microsphere is reinforced by disc-shaped crystalline hectorite nanosheets on the inside and lubricated by in situ formed molecular brushes on the outside, thereby solving the paradox of the mutual exclusion of "elasticity" and "lubrication" in inanimate hydrogels.
[0015] The present invention uses microfluidics and surface grafting polymerization techniques to develop biodegradable hydrogel microspheres with internal reinforcement and external lubrication. These microspheres are designed to minimize hydration penetration and prevent water loss, thereby solving the challenging paradox of the mutual exclusion of "elasticity" and "lubrication". First, through strong electrostatic / hydrogen bonding interactions, hectorite nanosheets are uniformly dispersed in the GelMA base segment in an intercalated structure, and polymer chains grow near the sheets through photo-initiated free radical polymerization, resulting in uniform distribution of tension between network segments and enhanced microsphere elasticity. At the same time, the multilayer structure of hectorite creates "living and movable" physical restrictions by filling the interlayer space, thereby restricting the free movement of water molecules and preventing them from penetrating into the polymer framework. Subsequently, poly (2-methacryloyloxyethyl phosphorylcholine) (PMPC) molecules are chemically grafted to the surface of the microspheres through surface grafting polymerization technology. Through the "active and dynamic" charge dipole interaction with water molecules, a hydrated lubricating layer is formed, and finally the construction of degradable elastic / lubricated hydrogel microspheres is achieved.
[0016] The hectorite nanosheets in the present invention act as "living" and "mobile" cross-linking points, providing physical confinement by occupying the interlayer space, thereby preventing active water from penetrating into the polymer framework and maintaining substantial cohesion. At the same time, the "active and dynamic" communication between the molecular brush and the water molecules through charge-dipole interactions significantly enhances sustainable lubrication. This "living" design makes the elastic modulus of the microspheres controllable between 14Pa and 4000Pa, and the friction coefficient adjustable between 0.12 and 0.04. The excellent performance of the hydrogel microspheres of the present invention in reducing cartilage friction and slowing the progression of osteoarthritis was further confirmed by both in vitro and in vivo experiments. Therefore, this new collaborative design strategy solves the challenge of balancing "elasticity" and "lubrication", paving the way for the application of hydrogels in pharmaceuticals, medical care, and mechanical lubrication.
[0017] In addition, as shown in the comparative examples of the present invention, the inventors have tried to replace methacrylated gelatin with methacrylated hyaluronic acid during the research process. It was found that the elastic modulus of the microspheres prepared under the system of the present invention was significantly lower, and thus it was impossible to obtain hydrogel microspheres with high elasticity and high lubricity.
[0018] At the same time, the inventors also tried to prepare hydrogel microspheres by directly mixing and cross-linking the raw materials in the system of the present invention through a one-pot method. The results showed that the elastic modulus of the hydrogel microspheres prepared by the one-pot method was also significantly lower, and it was still impossible to obtain hydrogel microspheres with high elasticity and high lubricity.
[0019] Furthermore, the preparation method of the photo-crosslinked GelMA monomer in step (1) is to react a gelatin solution with methacrylic anhydride and mix the resultant with a photoinitiator to obtain a photo-crosslinked GelMA monomer solution.
[0020] Furthermore, in step (2), the weight ratio of the hectorite nanosheets to the GelMA monomer is 5:1 to 5. The above weight ratio used in the present invention has been found through experiments that if the ratio is reduced, the elasticity of the microspheres cannot be increased. If the ratio is increased, the viscosity conditions of the microfluidic liquid cannot be met.
[0021] Furthermore, in step (2), the diameter of the hectorite nanosheets is 20-50 nm and the thickness is 1-2 nm.
[0022] Furthermore, the concentration of the GelMA monomer solution in step (2) is 4-7 wt %.
[0023] Furthermore, in step (3), the weight ratio of 2-methacryloyloxyethyl phosphorylcholine, acrylamide and laponite nanosheets is 0.5-2:0.5:1-5.
[0024] The second object of the present invention is to provide hydrogel microspheres prepared by the method as described above, wherein the hydrogel microspheres have both high elasticity and super lubricity.
[0025] Furthermore, the elastic modulus of the hydrogel microspheres is between 14Pa and 4000Pa, and the friction coefficient is between 0.04 and 0.12.
[0026] The third object of the present invention is to provide the application of the hydrogel microspheres as described above in the fields of pharmaceuticals, medical treatment and mechanical lubrication.
[0027] Furthermore, the hydrogel microspheres as described above are used in the preparation of medical materials or drugs for treating osteoarthritis.
[0028] The beneficial effects of the present invention are as follows:
[0029] (1) The present invention obtains a biodegradable hydrogel microsphere with both high elasticity and super lubricity, which solves the contradiction between "elasticity" and "lubricity" in hydrogel microspheres and successfully realizes the construction of degradable elastic and lubricating hydrogel microspheres;
[0030] (2) The hydrogel microspheres obtained by the present invention have the remarkable effect that the elastic modulus is controllable between 14Pa and 4000Pa, and the friction coefficient is adjustable between 0.12 and 0.04.
[0031] (3) The hydrogel microspheres of the present invention have excellent performance in reducing cartilage friction and slowing down the progression of osteoarthritis. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 (A) GelMA monomer 1 H NMR spectrum; (B) hydrated particle size of GL1 microspheres; (C) bright field microscopy image of GL1 microspheres; (D) XRD spectrum; (E) SEM images of laponite (left) and GL1 microspheres; (F) EDS spectrum of GL1; (G) rheological curve of the hydrogel. The rheological experiments were carried out at a constant frequency of 10 rad / s and a strain of 1% at 25°C.
[0033] Figure 2 As shown in the figure: (A) Optical image of hydrogel under pressure and schematic diagram of viscoelastic properties of microspheres; (B) Compression curve of GL hydrogel; (C) Compressive strength and (D) cyclic compression curve; The compression test was carried out at a speed of 2 mm / min; (E) Molecular dynamics simulation of GelMA-Laponite composite material and results of (FH) intermolecular force and (IK) hydrogen bond number; (L) Schematic diagram of compression simulation of GeMA-Laponite composite material and (MN) compression curve.
[0034] Figure 3 As shown in the figure: (A) XPS spectrum of GL1M0.5; (B) hydrogel swelling curve; (C) rheological curve of GL4M2; (D) schematic diagram of lubrication test of hydrogel microspheres; (EH) friction coefficient of hydrogel microspheres under different parameters and (IJ) corresponding wear volume of substrate.
[0035] Figure 4 Figure 2: (A) Representative images of live / dead cell staining in microspheres co-cultured with bone marrow mesenchymal stem cells (BMSCs); and (BC) corresponding live cell counts; (D) Representative images of live / dead cell staining in microspheres co-cultured with chondrocytes; and (EF) corresponding live cell counts; (n=3, *, # indicate comparison with control group and sham operation group, respectively, p<0.05).
[0036] Figure 5Figure 2: (A) Representative images of Alcian Blue and Safranin O staining of microspheres co-cultured with bone marrow mesenchymal stem cells, with (BC) related statistical data; (D) Expression level of type II collagen in bone marrow mesenchymal stem cells and representative immunofluorescence images; and (EF) corresponding fluorescence intensity; (G) qRT-PCR detection results of cartilage-specific genes Col II, Aggrecan and Sox9; (n=3, * indicates p<0.05 compared with the control group).
[0037] Figure 6 Figure 3: (A) Application of microspheres in OA cartilage regeneration; the viscoelasticity and lubrication properties of the microspheres effectively reduced the friction and wear of the cartilage. At the same time, the dissociation of laponite released KGN, which significantly promoted cartilage regeneration; (B) Macroscopic evaluation of knee specimens, showing representative views of the femoral condyle and tibial plateau of each experimental group, with cartilage defects or damaged areas indicated by blue arrows; (C-D) Outerbridge scores and relative cartilage defect area results of each experimental group; (n=3, * and # indicate comparison with the control group and sham operation group, respectively, p<0.05).
[0038] Figure 7 The following are: (A) X-ray images; AP: frontal view, LAT: lateral view; (B) KL score results of each group; (C) Micro-CT images; showing representative three-dimensional reconstructions and horizontal slices of the tibia side of each group; (D) Bone mineral density results of the knee joints of each group; (E) BV / TV results of the knee joints of each group; (n=3, *, # indicate comparison with the control group and sham operation group, respectively, p<0.05).
[0039] Figure 8 (A) Representative images of H&E staining, TB staining, Safranin O staining, and type II collagen immunohistochemistry of each group; (BD) Quantitative analysis of MMP13, Collagen II, and gag-positive cells; (n=3, *, # indicate comparison with the control group and sham operation group, respectively, p<0.05).
[0040] Fig. 9 The rheological curve of HAMA-Laponite hydrogel microspheres prepared by replacing the system in Comparative Example 1.
[0041] Fig.10 The rheological curve of the hydrogel microspheres prepared by the one-pot method in Comparative Example 2 is replaced.
[0042] Fig.11Schematic diagram of the design and application of the hydrogel microspheres of the present invention; (A) Degradable elastic and lubricating hydrogel microspheres are prepared by microfluidics technology. The lithium laponite nanodisks are used as multifunctional physical crosslinkers and nanoenhancers, which are entangled with the GelMA-based polymer chains through electrostatic and hydrogen bonding interactions, and serve as physical crosslinkers of the hydrogel microspheres; Subsequently, the PMPC molecules are chemically grafted onto the surface of the microspheres by surface grafting polymerization technology; (B) The polymerization process of the monomer in the lithium laponite aqueous solution. During the free radical polymerization process, the polymer chains initially grow from the surface of the lithium laponite disks and gradually extend to the surfaces of other lithium laponite disks to form an organic / inorganic polymer network bridged by nanodisks; (C) Schematic diagram of the lubrication and viscoelasticity of the microspheres. The heterogeneous charge distribution of lithium laponite is entangled with the polymer chains through electrostatic and hydrogen bonding interactions, which significantly improves the mechanical strength of the microspheres; In addition, the PMPC molecular brushes on the surface of the microspheres form a short-range ordered hydration layer by interacting with the charge dipoles of water, thereby achieving shear lubrication. In addition, the layered structure of lithium laponite acts as a physical barrier for molecular transport, limiting the free diffusion of water molecules. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0044] Example 1
[0045] 1. Experimental methods and characterization
[0046] 1. Experimental materials and sources
[0047] The small molecule compound Kartogenin (KGN) was purchased from Med Chem Express (USA); reagents such as 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), ammonium persulfate, 2-methacryloyloxyethyl phosphorylcholine (MPC), methacrylic anhydride (MA) and acrylamide were prepared using raw materials provided by Aladdin; gelatin was purchased from McLean; and lithium laponite nanosheets were purchased from Nanocor.
[0048] (II) Preparation method of microspheres
[0049] (1) Synthesis of GelMA monomer
[0050] The synthesis method of GelMA monomer is as follows: 20 g of gelatin was dissolved in 200 ml of PBS, and then 6 ml of MA was gradually introduced into the gelatin solution using a syringe pump (Lead Fluid, China); after reacting for 2 hours, the obtained GelMA solution was dialyzed with deionized water before freeze-drying.
[0051] (2) Preparation of GL and GLK microspheres
[0052] Microspheres were prepared using microfluidic technology, and the detailed composition of each group of microspheres is shown in Table 1. Briefly, the aqueous hydrogel precursor solution (5wt% GelMA, 0.5wt% acrylamide, 0.5wt% photoinitiator, a certain amount of laponite and KGN) and the microfluidic oil phase (paraffin oil mixed with 5wt% Span 80) were introduced into the inlet of the flow focusing microfluidic device, respectively. At the intersection, pre-gel droplets were formed by shear force and hydrophobic interaction. Subsequently, the generated droplets were exposed to UV radiation to induce cross-linking of the microgels. Subsequently, the collected microspheres were rinsed three times with acetone and deionized water to remove excess oil phase and other additives.
[0053] (3) Grafting MPC onto microspheres
[0054] 100 mg of microspheres were dissolved in 10 ml of distilled water. Subsequently, 30 mg of ammonium persulfate and 100-300 mg of MPC were added to the solution in sequence at 60°C. The resulting mixture was stirred for 8 hours under a nitrogen atmosphere. Then, the solution was centrifuged to remove impurities.
[0055] Table 1 Composition of hydrogel microspheres
[0056]
[0057] The raw material codes in the above table are as follows: GelMA is methacrylated gelatin, Acrylamide is acrylamide, Laponite is lithium soapstone, and MPC is 2-methacryloyloxyethyl phosphorylcholine.
[0058] (III) Material characterization methods
[0059] 1. Characterization of microsphere appearance
[0060] The surface morphology of the microspheres was characterized by scanning electron microscopy (SEM, Hitachi S-4800), and the same samples were examined by SEM and the elemental surface chemistry was evaluated by EDS (Thermo Scientific, USA). The chemical structure of GelMA was determined by nuclear magnetic resonance (NMR, 400 MHz, Avance III, Germany). In addition, the morphology and particle size of the microspheres in aqueous solution were observed using phase contrast optical microscopy (PCOM, Nikon, Japan). The elemental composition of GLKM microspheres was analyzed by X-ray photoelectron spectroscopy (XPS, Thermo Nexsa, US).
[0061] 2. Rheological properties analysis
[0062] All rheological analyses were performed in an AR2000 rheometer (TA Instruments, New Castle, DE). Hydrogel tests were performed using a 40 mm steel cone and plate geometry with a gap distance of 200 μm. Rheological experiments were performed at a constant frequency of 10 rad / s and a strain of 1% at 25 °C. All rheological experiments were performed in triplicate.
[0063] 3. Compression mechanics test
[0064] Compression tests were performed on hydrogel cylinders with a diameter of 10 mm and a height of 6 mm using an Instron 5542 mechanical testing machine equipped with a 100 N load cell at a compression rate of 2 mm / min. At least three samples were tested under each condition and the compressive stress-strain curves were recorded.
[0065] 4. X-ray diffraction (XRD)
[0066] The wavelength used is The crystal structure of the sample was analyzed by X-ray diffraction (XRD, RigakuMiniFlex600, Japan) at 40 kV and 200 mA using Cu Kα radiation. The scanning range was 5° to 60° (2θ) with a step size of 1° / min. The interplanar spacing of each diffraction plane was determined using the Bragg law:
[0067] 2dsinθ=nλ (1)
[0068] Where λ is the wavelength of the copper anode source θ is the diffraction angle of each refractive index diffraction surface.
[0069] 5. Tribology test
[0070] The lubrication properties were measured using a universal material tester (UMT-2, Bruker, Germany) in reciprocating mode (amplitude: 3 mm) as described in previous studies. All tribological experiments were performed using a ball-on-disk friction test mode with Si3N4 balls and polytetrafluoroethylene (PTFE) as the upper and lower friction pairs. PBS was used as a buffer in the experiment to ensure good stretching of the microspheres. Friction tests were carried out for 10 min at a certain lubricant concentration (5.0 mg mL-1), different loads (1-3 N) and frequencies (0.5-3 Hz). The time-dependent friction coefficient (COF) curves were recorded during the test. After the friction test, the surface roughness of the samples was observed using confocal phase shift-microxam-3d to evaluate the wear performance.
[0071] 6. Expansion test
[0072] A freeze-dried spherical hydrogel, 1 cm in diameter, was immersed in 3 ml of PBS solution. After the specified duration, it was taken out and weighed. The difference in mass indicates the amount of water absorbed by the dried hydrogel. At least three samples were tested.
[0073] 7. Molecular dynamics (MD) simulation
[0074] MD simulations were performed using GROMACS (version 2020.6) and the structures of the 100 repeating unit polymer and laponite were built in Materials Studio. The structures of the 100 repeating unit polymer and laponite were generated in Materials Studio software. The GelMA polymer was modeled using the Amber99sb force field, while the laponite structure was described using a universal force field. First, the geometry of the polymer repeating units was optimized by density functional theory calculations using the b3lyp / 6-31g(d) method, followed by RESP charge calculations using the Multiwfn program. Subsequently, the polymer structure was relaxed at 500 K using stochastic mechanics calculations. The random coil-like eight chains were then inserted into a 10 × 10 nm cubic box centered on the laponite. After thousands of steps of energy minimization, there was a 10 ns equilibration period before water was added to dissolve the entire system. The production run was 100 ns in the NPT ensemble, and nonequilibrium box deformations were performed at a rate of 1 nm / ns over a period of 10 ns to measure the mechanical properties. The temperature was controlled at 300 K using the Nose-Hoover method. Non-bonded interactions were treated with a 1.2 nm cutoff scheme, and long-range electrostatic interactions were treated with the particle mesh Ewald method with a Fourier spacing of 0.1 nm. Covalent bonds involving hydrogen atoms were constrained using the LINCS algorithm.
[0075] 8. Cell experiments
[0076] 1) Cell culture: 3rd and 4th generation bone marrow mesenchymal stem cells (BMSCs) and 1st generation chondrocytes of SD rats were used for cell culture. DMEM / F-12 (Gibico, USA) medium was supplemented with 10% bovine serum and 100 U·mL -1 Penicillin and 100 g mL -1 Streptomycin, prepare complete cell culture medium. When the hydrogel microspheres are introduced into the system, the Transwell co-culture system is used. In this experiment, cells are inoculated in the lower chamber, and hydrogel microspheres with different drug loads are added to the upper chamber. Since the pore diameter on the Transwell membrane is 0.4μm, this allows the therapeutic drugs and the degradation products of the hydrogel microspheres to enter the lower chamber through the pores, thereby exerting their therapeutic effects.
[0077] 2) Biocompatibility assessment: Live / dead cell staining (Beyotime, China) was performed, and bone marrow mesenchymal stem cells or chondrocytes were seeded in Transwell 12-well plates at a density of 1×104 cells / well, and GM, GLM, and GLKM were supplemented in the upper chamber. Live / dead cell staining was performed on days 1, 3, and 5. CCK-8 assay (Beyotime, China) was performed: cells were seeded in the lower chamber of Transwell 96-well plates at a density of 2×10 3 Cells / well. Add drug-loaded hydrogel microspheres into the upper chamber according to the above steps. Perform CCK8 staining on days 1, 3, and 5, and analyze OD values.
[0078] 9. Evaluation of cartilage differentiation
[0079] To induce chondrogenic differentiation, 10 ng / mL TGF-β3 and 1% ITS were added to DMEM / F-12, and FBS was reduced from 10% to 5%. BMSCs were seeded into Transwell 12-well plates at a density of 1*104 cells per well, and then the drug-loaded hydrogel microspheres were added to the upper chamber of the culture system. PBS was added to establish a control group, and the positive control group consisted of chondrocytes. The culture medium was changed every two to three days. The Transwell co-culture system allows for the sustained release of encapsulated drugs in the hydrogel microspheres. BMSCs were induced for two weeks and then evaluated using the following methods:
[0080] a) Alcian blue staining (Solarbio). Add acidified solution and soak for 3 minutes, then add Alcian blue staining solution and react for 30 minutes. Then rinse the sample with running distilled water for 5 minutes and observe under a bright field microscope. The degree of blue indicates the degree of cartilage differentiation. The darker the blue, the more obvious the cartilage differentiation.
[0081] b) Saffron O staining (Solarbio). After adding 4% paraformaldehyde and incubating for 10 minutes, the cells were treated with Safranine O staining solution for 2 minutes. The cells were then rinsed with distilled water for 1 minute and observed under a bright field microscope. The degree of red indicates the degree of cartilage differentiation. The darker the red, the more obvious the cartilage differentiation.
[0082] c) Immunofluorescence staining. The cells were fixed with 4% paraformaldehyde for 20 minutes, then treated with 0.2% TritonX-100 for 10 minutes and 5% skim milk for 2 hours. Then they were incubated with rat type II collagen antibody (1:200) and secondary antibody (1:500) at 4°C for 1 hour. The cytoskeleton and nucleus were stained, and the cells were observed under a laser scanning confocal microscope.
[0083] d) Quantitative reverse transcription polymerase chain reaction (qRT-PCR). RNA was extracted by chloroform and isopropanol, reverse transcribed into cDNA using a reverse transcription kit (Takara, Japan), and finally amplified using a qRT-PCR kit (Takara, Japan). Finally, GAPDH was used as a reference gene, and the expression of type II collagen (Col II), Aggrecan, and SOX9 was calculated using the CT method. The primer sequences of the above four genes are shown in Table 2 below:
[0084] Table 2
[0085]
[0086]
[0087] 10. Animal Experimentation
[0088] All animal experiments were approved by the Animal Research Committee of Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, approval number: SYXK 018-0027.
[0089] a) The establishment of the SD rat medial meniscus instability (DMM) osteoarthritis model was carried out in accordance with the guidelines established by the Animal Research Committee of Ruijin Hospital, School of Medicine, Shanghai Jiao Tong University. Anesthesia was performed by intraperitoneal injection of 3% sodium pentobarbital (40 mg kg-1). After successful anesthesia, the DMM model was surgically constructed, and the right knee joint was selected as the experimental side. At 2, 4 and 6 weeks after modeling, the drug-loaded hydrogel microspheres were injected into the knee joint. The animals were divided into 6 groups: sham operation group, control group, GelMA group, GM group, GLM group and GLKM group. The injection volume was 200 μL, and the sham operation group no longer underwent intra-articular injection. The control group was given PBS with pH = 7.4.
[0090] b) Radiological evaluation: The knee joint was resected 8 weeks after modeling. The severity of knee osteoarthritis was evaluated by X-ray using the Kellgren-Lawrence (KL) score. In addition, micro-CT was used to measure the bone mineral density (BMD) and subchondral bone volume fraction (BV / TV) on the tibial side.
[0091] c) Evaluation of gross appearance of knee joint: In order to more intuitively study the therapeutic effect of GLKM on knee osteoarthritis, we evaluated the gross appearance of the knee joints of SD rats. After carefully removing the surrounding muscles, ligaments, and meniscus tissues, the femoral condyle and tibial plateau were separated, and then the articular cartilage was evaluated under direct visual inspection. The Outerbridge score was used to quantify the condition of the tibial plateau cartilage. Subsequently, the specimens were photographed, and the relative lesion area of the tibial plateau was quantified using ImageJ software. The software measures the area of damaged cartilage on the tibial plateau as a percentage of the entire tibial plateau area.
[0092] d) Histological and immunohistochemical evaluation: The decalcified knee joint specimens were paraffin-embedded, sectioned, and stained with H&E, saffron o-fast green, toluidine blue, and type II collagen immunohistochemical staining. The articular cartilage degeneration of the specimens was then observed and evaluated under a bright field microscope and quantitatively analyzed.
[0093] 11. Data statistics and analysis
[0094] All experimental data are presented as mean ± standard deviation, and independent experiments were repeated at least three times. The experimental data were statistically analyzed and the corresponding graphs were generated. Tukey's multiple comparison test was used to compare multiple groups. p < 0.05 was considered statistically significant. For quantitative images, at least three images were randomly observed, and one representative image was selected for display.
[0095] 2. Experimental Results and Discussion
[0096] 1. Preparation and characterization results of GL elastic microspheres
[0097] First, the photo-crosslinked GelMA monomer was successfully synthesized. Its structure is shown by 1 H NMR spectrum ( Figure 1 The presence of characteristic peaks in (A) was confirmed, especially between 5.34 ppm and 5.65 ppm, corresponding to the methacrylate vinyl group of methacrylic anhydride. Subsequently, customizable inorganic hectorite cross-linked hybrid hydrogel microspheres were prepared using microfluidic technology. The microspheres in Table 1 are named according to their respective components, and the size of the obtained microspheres is about 230 μm ( Figure 1 Chinese BC).
[0098] like Figure 1As shown, hectorite nanosheets are synthetic layered polyanions composed of silicate layers, in the shape of disks, with a diameter of about 20-50nm and a thickness of 1-2nm. These disks are negatively charged on the surface and positively charged on the edges, with unique inhomogeneous charge distribution and interlayer interactions. Due to its hydrophilicity and electrostatic interactions, hectorite can be dispersed into a single-layer sheet structure in aqueous solution, or form an intercalated structure similar to a "house of cards", thereby forming a tight bond with the polymer chain.
[0099] In order to determine the interaction mechanism between laponite and polymer chains, XRD analysis was performed on microspheres GL1 and GL4 containing 1 wt% and 4 wt% laponite. Figure 1 As shown in D, pure hectorite exhibits characteristic diffraction peaks at 2θ=6.05, 19.99, 26.30, 34.89, and 53.17, corresponding to the five crystal planes (001), (100), (005), (110), and (511), respectively. For GL1, no obvious hectorite peaks were observed, indicating that at low concentrations, hectorite falls off from its layered structure and is evenly dispersed in the polymer network. In contrast, GL4 has obvious hectorite peaks at 2θ=19.51, 34.63, and 53.10, except for the absence of the (005) crystal plane.
[0100] In addition, calculations based on the Bragg equation revealed different degrees of changes in the interplanar distance. For example, the interplanar spacing d(100) increased from the original 0.085nm to 0.126nm. This may be due to the fact that some hectorite particles penetrated into the polymer chain in a "house of cards" embedded form, acting as physical cross-linkers and providing physical cross-linking sites for the growth and connection of molecular chains. That is, the polymer chains grew on the surface of the disks to form a chain network bridged by the disk particles until they terminated by combining with free radicals of other chain segments. The extension and expansion of the interlayer polymer chains increased the interplanar distance. In addition, SEM / EDS analysis showed that the hectorite disks and GL1 microspheres had a multilayered lamellar structure, while the GL1 microspheres had a porous honeycomb structure with no obvious accumulation of lamellar particles on the surface, indicating that the hectorite was uniformly embedded in the GelMA-based polymer chains as cross-linking points.
[0101] In order to investigate the effect of laponite concentration on the viscoelastic properties of GelMA-based networks, dynamic frequency sweep tests were performed on cylindrical samples with a diameter of 40 mm and a thickness of 2 mm. Figure 1Figure G shows the change of elastic modulus (G′) and loss modulus (G”) of the hydrogel over time. It can be seen that the G′ values of all hydrogels are greater than the G” values, confirming the elastic behavior of the hydrogel. With the increase of lithium laponite concentration, the G′ value increased significantly from 14Pa to 4000Pa, while the loss factor tanδ (tanδ=G′ / G”) decreased from 0.22 to 0.052, indicating that a strong interaction was formed between lithium laponite and GelMA, thereby enhancing the viscoelasticity of the gel network. In addition, the increase in G” indicates that the viscous dissipation in the hydrogel is higher and the chemical bonds are reversible.
[0102] In order to observe the viscoelasticity of microspheres macroscopically, Figure 2 As shown in Figure A, a spherical hydrogel with a diameter of 10 mm was prepared, which contained 2wt% (for dyeing) and 4wt% of hectorite, namely GL2 and GL4 microspheres, and a certain pressure was applied in the vertical direction. It can be clearly seen from the figure that under almost the same pressure, GL2 is softer and deforms more than GL4, indicating that increasing the hectorite content effectively enhances the viscoelasticity of the hydrogel microspheres. And after the external force is removed, the spherical structure of GL4 can quickly recover itself.
[0103] In addition, the elastic properties of the microspheres were verified using a universal testing machine ( Figure 2 From the compressive stress-strain curve ( Figure 2 As can be seen from Figure B, with the increase of lithium laponite content, the compressive strength of the hydrogel gradually increases. Among them, the compressive strength of GL4 hydrogel is as high as 55kPa at 40% strain. In addition, in the stress-strain cycle curve ( Figure 2 In the CD), the different cycle curves almost overlap, indicating low hysteresis. This shows that GL4 can effectively avoid stress concentration and energy dissipation under external pressure and has excellent anti-fatigue performance. This can be attributed to the fact that hectorite acts as an active center of reversible non-covalent bonds, providing abundant hydrogen bonding sites and electrostatic interactions with polymer chains, increasing the number of cross-linking points, and forming hierarchical chain entanglements. Under the synergistic effect of hydrogen bonding / electrostatic interactions, the polymer segments are effectively fixed, preventing excessive slippage and breakage of the segments under pressure, thereby minimizing energy dissipation under load and effectively improving the mechanical properties of the hydrogel.
[0104] To further elucidate the interaction between laponite and GelMA polymer chains, molecular dynamics simulations were performed. Figure 2As shown in Figure E, a monolayer consisting of 100 laponite and GelMA molecules was constructed by calculation. The Amber99sb force field was used to simulate the GelMA polymer, while the general force field was used to characterize the laponite structure. It can be seen that after relaxation treatment, the GelMA polymer chains are evenly dispersed in the water environment and surrounded by abundant water molecules. However, after the addition of laponite, the cohesive force within the GelMA polymer chains is significantly enhanced, leading to aggregation. In addition, as the contact time between GelMA and water molecules increases, the Coulomb force, van der Waals force, and the number of hydrogen bonds between GelMA and water molecules begin to decrease and gradually stabilize, indicating that the GelMA-water configuration gradually transitions to an equilibrium state ( Figure 2 Middle F).
[0105] After the hectorite was introduced into the system, GelMA quickly combined with it, which was manifested by a rapid increase in the number of Coulomb forces, van der Waals forces, and hydrogen bonds ( Figure 2 In addition, from Figure 2 It can be seen from the IK that the total interaction energy between the GelMA-hectorite mixture and water is lower than that of the pure dispersion, and the number of hydrogen bonds between the two decreases from about 1000 initially to about 665, indicating that GelMA is more easily bound to hectorite. These results indicate that in aqueous solution, the GelMA polymer chains tend to aggregate on and around the surface of the hectorite disks through strong electrostatic forces, Coulomb forces, and hydrogen bonding interactions, thereby forming a denser polymer layer. This also suggests that during the free radical polymerization process, the GelMA polymer chains initially grow from the surface of the hectorite disks and gradually extend to the surfaces of other hectorite disks, forming an organic / inorganic polymer network bridged by nanodisks.
[0106] In addition, computer compression simulations of the GelMA-hectorite and GelMA systems were performed ( Figure 2 Specifically, the eight chains were initially placed in a 10 × 10 nm cubic box centered on a random coil structure of laponite. After a large number of energy minimization steps, there was a 10 ns equilibration period before more than 24,000 water molecules were introduced to solvate the entire system. Under the NPT system, the production time was extended by 100 ns. After this, the box was subjected to non-equilibrium stretching and compression at a rate of 1 nm / ns for 10 ns and 5 ns, respectively. The strain-stress simulation curves corresponding to these processes show that the mechanical properties of the GelMA network are significantly enhanced due to the presence of laponite.
[0107] 2. Preparation and characterization of GLM elastic and lubricating microspheres
[0108] Hydrogels are polymer materials composed of a hydrophilic polymer network. However, the hydration capacity of traditional hydrogels is inversely proportional to their load-bearing capacity. Highly hydrated hydrogel materials are too soft and easily deformed during high-load shear. Conversely, hydrogels with excellent mechanical properties have poor surface hydration properties, which hinders their lubrication ability.
[0109] In order to obtain GLM microspheres with elasticity and lubricity, GL microspheres were modified with 2-methacryloyloxyethyl phosphorylcholine (MPC). Poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) is an amphoteric polymer that forms a short-range ordered hydration layer on its surface through strong interactions between anionic and cationic groups and water, thereby achieving lubrication. XPS spectrum ( Figure 3 A) in the middle confirms the successful introduction of PMPC, with its characteristic peak located at 133.1 eV.
[0110] Typically, increased gel hydration leads to swelling of the polymer segments, which reduces their load-bearing capacity. We analyzed by swelling tests whether the introduction of PMPC leads to extensive water penetration into the microspheres and subsequently into the polymer network. Figure 3 As shown in Figure B, the addition of PMPC enhances the water absorption capacity of the gel, while the increase in the content of hectorite reduces the swelling of the gel. This may be due to the following reasons: (1) Molecular simulation results show that the polymer chains tend to bind tightly to hectorite, thereby inhibiting the entry of water molecules into the polymer framework; (2) The layered structure of hectorite acts as a physical barrier to molecular transport, limiting the free migration of water molecules. Therefore, due to the inhibition of swelling, the elastic modulus of GL4M1 is similar to that of GL4, indicating that the addition of PMPC does not significantly reduce the mechanical strength of the gel ( Figure 3 Middle C).
[0111] The friction test was carried out using the UMT-3 reciprocating friction tester to analyze the effect of PMPC on the lubrication performance of microspheres. Figure 3 As shown in Figure DH, the friction coefficient of the microspheres was tested under different frequencies, loads (simulating the frequency and load of the joints when humans walk / run) and substrates. We found that under these test conditions, the friction coefficient (COF) of GLM microspheres was lower than that of GL, which was due to the fact that the zwitterions of PMPC locked a large number of water molecules through charge-dipole interactions to form a stable hydrated lubrication layer. In addition, as the reciprocating friction frequency and load increased, the COF value of GLM was significantly lower than that of GL, which may be due to the combined effect of its lubrication mechanism, hydrodynamic lubrication and boundary lubrication.
[0112] In addition, a profilometer was used to observe the surface morphology of the steel substrate after the friction test ( Figure 3In the IL, the GelMA microsphere solution as a lubricant showed the highest wear, while the GLM showed the least wear. The results show that the GLM has good elasticity and lubrication properties.
[0113] 3. Evaluation of in vitro chondrogenesis
[0114] Osteoarthritis (OA) is a common joint disease characterized by cartilage wear, and its pathogenesis may be related to excessive mechanical load and insufficient joint lubrication. Mechanical overload leads to cartilage damage, inducing overexpression of decomposition enzymes, leading to chondrocyte apoptosis and extracellular matrix degeneration, thereby increasing articular cartilage friction, further aggravating joint inflammation, and forming a vicious cycle.
[0115] In order to evaluate the feasibility of the above-mentioned GLM elastic and lubricating microspheres for OA treatment, the biocompatibility of the microspheres was evaluated by co-culture with bone marrow mesenchymal stem cells (BMSCs) and chondrocytes using CCK-8 and live / dead staining methods. Notably, in order to synergistically promote cartilage repair and regeneration, we took advantage of the high specific surface area and dual charge properties of hectorite and prepared GLKM by efficiently loading Kartogenin (KGN) (performed in the form of GL4M2 microspheres). KGN is a small molecule drug that has the pharmacological effect of promoting chondrogenic differentiation of MSCs. Figure 4 As shown, all experimental groups showed positive effects on cell growth and proliferation, indicating that the above biomaterials have good biocompatibility. Alcian Blue and Safranin O staining results preliminarily showed ( Figure 5 AC) GLKM has the ability to promote chondrogenic differentiation of bone marrow mesenchymal stem cells. At the same time, immunocytochemical method observed that the expression of Collagen II in the GLKM group was the highest ( Figure 5 EF), qRT-PCR results showed that the expression of Collagen II, Aggrecan and SOX9 in the Laponite / KGN (LK) and GLKM groups also increased ( Figure 5 These results can be explained by the sustained release of KGN, the synergistic interaction between cells and laponite, and the dissociation of laponite ions. Therefore, GLKM exhibited the best chondrogenic differentiation ability because its 3D porous network enabled sustained drug release.
[0116] 4. Evaluation of cartilage protection and regeneration in a rat osteoarthritis model
[0117] Elasticity / lubrication properties are widely present in nature and are crucial to the physiological functions of biological interfaces, especially load-bearing parts such as joints with complex biomechanical environments. Among them, the stress buffering and friction reduction provided by the high elasticity / high lubrication properties of articular cartilage are indispensable. If the elasticity and lubrication functions of cartilage are unbalanced, stress will be concentrated on the surface of cartilage during mechanical loading, resulting in increased friction and wear, irreversible degeneration of cartilage, and ultimately the occurrence of osteoarthritis.
[0118] In order to verify the protective and repair effects of the elastic lubricating microspheres on articular cartilage in the OA environment, a rat OA model based on medial meniscus instability (DMM) was established. Intra-articular injections were performed on the knee joints of rats at 2 and 4 weeks after modeling, and all rats were euthanized at 8 weeks to further evaluate the therapeutic effect ( Figure 6 First, the gross appearance of the rat knee joints was evaluated to determine the protective effect of each group on articular cartilage. Figure 6 As shown in BD, the tibial plateau cartilage damage was obvious in the control group, while the damage area and cartilage surface damage depth were reduced in the GLKM group. The Outerbridge score was 1.2±0.20 points, while that in the control group was 3.60±0.25 points, indicating that the cartilage damage in the GLKM group was significantly improved.
[0119] Radiological evaluation ( Figure 7 Middle AB) shows that the knee joints in the control group showed extensive osteophyte formation, subchondral bone destruction, significantly narrowed joint space, and enhanced epiphyseal radioactivity, indicating that OA modeling was successful. However, after GLKM treatment, the knee joints showed mild narrowing of the joint space, minimal osteophyte formation, and greatly increased subchondral and epiphyseal bone density, indicating that GLKM has a good cartilage protection effect.
[0120] In addition, Micro-CT showed similar results ( Figure 7 Figure 5 (Central CE). Bone density was significantly increased to 0.68 ± 0.04 in the GLKM group compared to the control group (Bone density = 0.44 ± 0.05). The same trend was also observed in BV / TV. The observed phenomenon may be attributed to the elastic properties of GLKM, which contributes to stress buffering of articular cartilage. In addition, its lubricating properties help prevent friction and wear caused by increased friction coefficient of cartilage surface. In addition, the synergistic effect of KGN promotes cartilage repair, ultimately leading to the successful attenuation of cartilage degeneration.
[0121] Histological evaluation was also performed to further evaluate the therapeutic effect of GLKM. H&E and toluidine blue staining (TB) ( Figure 8) showed that the extent of cartilage damage in the GelMA group was comparable to that in the control group, with the fibrous structure of the entire cartilage layer destroyed and a decrease in the chondrocyte count. For the GM, GLM, and GLKM groups, we observed a decrease in the depth of cartilage damage and an increase in the number of chondrocytes growing in clusters. Safranin O / fast green and Col II immunofluorescence staining showed that the expression of glycosaminoglycan (GAG) and type II collagen was the highest in the GLKM-treated group. These results suggest that the elasticity and lubrication properties of therapeutic microspheres play an important role in protecting cartilage.
[0122] Overall, GLKM exhibited excellent efficacy in promoting cartilage tissue repair by combining its elastic properties to buffer stress, lubricating properties to reduce cartilage friction, and the synergistic effects of KGN in promoting cartilage formation.
[0123] Conclusion
[0124] The present invention combines microfluidics with surface graft polymerization to construct elastic lubricating hydrogel microspheres, which are cross-linked with inorganic hectorite nanosheets internally and grafted with PMPC externally. Hectorite with heterogeneous charge distribution characteristics increases the elastic modulus of the microspheres by two orders of magnitude through strong electrostatic and hydrogen bond interactions. The hydration of PMPC reduces the friction coefficient (COF) of the elastic microspheres from 0.12 to 0.04. The water-locking ability of PMPC and the physical barrier of hectorite are used to effectively inhibit the penetration and softening of water molecules into the polymer chain, so that the elasticity and lubricity of the hydrogel microspheres coexist.
[0125] In vitro experiments showed that the dissociation of hectorite and the sustained release of KGN synergistically promoted chondrogenesis of bone marrow mesenchymal stem cells. In a rat OA model, these elastic and lubricating hydrogel microspheres provided hydration lubrication and mechanical support under shear force, reduced friction and wear of the knee joint, and synergistically promoted cartilage regeneration, thereby effectively slowing the progression of OA. In conclusion, this type of elastic and lubricating microspheres is expected to treat medical conditions related to mechanical and lubrication imbalances.
[0126] Comparative Example 1
[0127] Referring to the method of Example 1, the formula of GL4 hydrogel precursor solution was: 5wt% GelMA, 0.5wt% Acrylamide, 0.5wt% photo-initiator, 4wt% Laponite and 5wt% GelMA in KGN was replaced with 5wt% HAMA, and the other conditions remained unchanged. The rheological curve of the obtained HAMA-Laponite microspheres was plotted. The results are shown in FIG. Fig. 9 It is shown that its elastic modulus is significantly smaller than that of GL4.
[0128] Comparative Example 2
[0129] Referring to the method of Example 1, a one-pot method was used to prepare GL4M2 hydrogel. The specific method is as follows: 5wt% GelMA, 0.5wt% Acrylamide, 0.5wt% photo-initiator, 4wt% Laponite, and 2wt% MPC were directly mixed and then photocrosslinked to obtain GL4M2 microspheres, and the rheological curve was obtained as shown in FIG. Fig.10 The results showed that its elastic modulus was significantly smaller than the elastic modulus of the GL4M2 hydrogel prepared in steps in Example 1.
Claims
1. A method for preparing hydrogel microspheres with both high elasticity and super lubricity, characterized in that: The following steps are involved: (1) Synthesizing photo-crosslinked GelMA monomer solution; (2) mixing the laponite nanosheets with the GelMA monomer solution obtained in step (1), and preparing laponite cross-linked hybrid hydrogel microspheres by microfluidic technology; (3) The hydrogel microspheres obtained in step (2) are modified by a surface grafting method using 2-methacryloyloxyethyl phosphorylcholine and acrylamide to obtain hydrogel microspheres having both high elasticity and super lubricity.
2. The method according to claim 1, characterized in that The preparation method of the photo-crosslinked GelMA monomer in step (1) is to react a gelatin solution with methacrylic anhydride and mix the mixture with a photoinitiator to obtain a photo-crosslinked GelMA monomer solution.
3. The method according to claim 1, characterized in that In step (2), the weight ratio of the hectorite nanosheets to the GelMA monomer is 5:1-5.
4. The method according to claim 1, characterized in that In step (2), the diameter of the hectorite nanosheets is 20-50 nm and the thickness is 1-2 nm.
5. The method according to claim 1, characterized in that The concentration of the GelMA monomer solution in step (2) is 4-7 wt %.
6. The method according to claim 1, characterized in that In step (3), the weight ratio of 2-methacryloyloxyethyl phosphorylcholine, acrylamide and laponite nanosheets is 0.5-2:0.5:1-5.
7. The hydrogel microspheres prepared by the method according to any one of claims 1 to 6, characterized in that: The hydrogel microspheres have both high elasticity and super lubricity.
8. The hydrogel microsphere according to claim 7, characterized in that: The elastic modulus of the hydrogel microspheres is between 14Pa and 4000Pa, and the friction coefficient is between 0.04 and 0.
12.
9. Use of the hydrogel microspheres prepared by the method according to any one of claims 1 to 6 or the hydrogel microspheres according to any one of claims 7 to 8 in the fields of pharmaceuticals, medical treatment and mechanical lubrication.
10. Use of the hydrogel microspheres prepared by the method according to any one of claims 1 to 6 or the hydrogel microspheres according to any one of claims 7 to 8 in preparing medical materials or drugs for treating osteoarthritis.
Citation Information
Patent Citations
Hydrogel microspheres for repairing bone defects and preparation method thereof
CN113181434A
Self-renewal hydrated lubricating drug-loaded hydrogel microspheres, preparation method and application thereof
CN113995891A
Tough gel-based drug delivery compositions and methods thereof
CN114423460A
Cited By
Low-temperature-resistant torsion wind energy shielding flexible cable and manufacturing method thereof
CN120636911A